RISK ASSESSMENT OF SHEEP AND GOAT POX SPREAD IN KAZAKHSTAN (Experimental biology, 2023)
Sheep and goat pox (SGP) disease is a highly contagious and dangerous viral infection, characterized by fever, formation of papular-pustular lesions in the epithelium of the skin and respiratory tract of small ruminants. This disease causes enormous damage to sheep breeding due to the death of animals, forced slaughter, loss of productivity, costs for veterinary and sanitary and quarantine measures. The causative agents are two closely related viruses: sheep pox virus and goat pox virus, belonging to the family Poxviridae, the genus Capripoxvirus. SGP is considered an endemic in Kazakhstan and SGP outbreaks have been registered in a number of regions both in our country and bordering states. The uncontrolled spread of this infection can be associated with colossal economic losses and significant damage of the image of our country as an exporter of lamb. Thus, it is important to monitore the epizootological situation of SGP in the country, control outbreaks of infection, and develop veterinary and sanitary measurements to adequately anticipate of the disease spread. Therefore, the purpose of this study is to perform risk analyses of SGP transmission in Kazakhstan. As a result of the research, the SGP risk factors, epizootological characteristics of this infection in Kazakhstan in the last 10 years, and the districts with high risks regarding the possible occurrence of large outbreaks of SGP were identified and the epizootic visualization map was created. This work provides valuable information on the importance of SGP control and prevention programs in Kazakhstan.
Keywords: epizootology, sheep pox, goat pox, virus, risk analysis.